RETRACTED: Anthropogenic transformation of the valleys of small rivers of the Chuvash Republic - Nikonorova Inna; Ilyin Vladimir; Ilyina Anastasia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001